ALAT PEMANTAU AIR GALON DAN PENGISI GELAS OTOMATIS BERBASIS ESP8266 - Henderi Henderi; Ageng Setiani Rafika; Rani Putri Merliasari (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2020)
Drinking water is very important for the human body, humans will lose concentration and even feel dizzy when lacking water. At the North Serpong District Office there are several locations for drinking gallons of water, but when someone wants to drink but the gallon water runs out the person must tell the officer about it, so the clerk will refill the gallon. When you want to drink you have to hold the glass and open the tap manually to fill the glass and then close it when it's full. This research was conducted using the SDLC method and Black Box testing. This study discusses about designing a gallon water monitor and automatic glass filler with Wemos D1 that uses the ESP8266 chip as a microcontroller, load cell as a detector for the weight of the remaining gallon water and the weight of glass, ultrasonic sensors to measure the distance of glass and servo motor to move the water tap lever . The rest of the gallon water can be monitored through the internet using a smartphone, notifications are sent when the remaining 2 liters of gallon water and the glass can be filled automatically as much as 250ml.